Зниження технологічних витрат електроенергії в розподільних електричних мережах - Омельчук, А. О. (Енергетика і автоматика, 2017)
UDC 621.313.32 THE TECHNOLOGICAL COST OF ELECTRIC POWER CUTTING IS IN DISTRIBUTIVE ELECTRIC NETWORKSA. Omelchuk Technological community and regime of generation, transmission, distribution and use of electricity requires consider reactive power compensation (PKK) as a joint event of PLE reduction and ensure the stability of the electrical system.The problem of reactive power balance in load of the system need to be addressed from consumer and distribution networks, where complete uncertainty due to the subjective attitude of consumers to the PKK to power.Feasibility task of selecting and placing power capacitors (CG) in the power grids divided into two components: support the balance of reactive power in electric networks (EM) and reduced power losses and electricity distribution networks.The purpose of research - optimization of parameters capacitors in electrical distribution networks.Materials and methods of research. Evaluating the effectiveness of the proposed methodology for regional energy companies considered by the example of solving the problem priority study of installing and determining the optimal capacity KU in the grid.As an example, the circuit is considered a network that includes the district transformer substation (RTP) voltage 35 ... 110/10 kV with five outgoing lines with voltage 10 kV transformer substations consumer closed (FTE) 10 / 0.4 kV .Justification of installing capacitor banks expedient to carry out in two stages: first place determined technologically possible placement, connection and operation of KU in the grid, such as switchgear (AC) 10 kV RTP-35 ... 110/10 kV switchgear 10 kV and 0.4 FTE, voltage switchgears 0 38 kV production facilities, etc. second stage, if necessary (for example, the problem of multiple or limit funds for energy-saving measure), is to determine the economic KU accommodation options in specific locations of electric network using performance reactive power compensation.Results. Power optimization criterion adopted CG feature reduced cost C, which contains two components:1) costs of KU owner of power networks - the cost of KU and their installation, annual maintenance and depreciation deductions;2) economic effect of reactive power compensation - reducing energy losses in the network owner.When solving the optimization problem of power KU considered that the voltage in load adopted unchanged, the impact on KU mode voltage does not count - a measure of the problem of optimization of KU, KU cost and power losses in KU accepted based on their capacity and voltage and depend on their capacity and voltage.To solve the problem of optimizing power KU, which is different from the problem of justification energy saving measures appropriate to use the reduced costs of reactive power compensation in the proposed network, adapted to current economic conditions.Justification technical solutions and assess the effectiveness of energy-saving projects offers a number of methods to carry out using indicators such as net income discounted CHDP index IP profitability, payback period and other current. Therefore, after the power of choice and type KU their efficiency as compared with other energy saving measures, is estimated above mentioned parameters.ConclusionsThe task of optimal compensation of reactive power in electric networks of regional energy companies it is advisable to decide by minimizing the objective function reduced costs, adapted to current market conditions of the economy.The optimal measure reactive power compensation (related to power KU reactive power load) in different parts of the electrical grid can vary from 0.45 to 0.98 ActingThe economic effect of reactive power compensation in the grid only one RTP voltage 35 ... 110/10 kV confirm the discounted net revenue and payback period CHDP Talk: CHDP normative for eight-year payback period varies from 1,48∙105 to 2,08∙106 UAH., and the payback period of 0.18 years even KU.Changing the design parameters and parameters of the grid mode of operation does not significantly affect the performance value of reactive power compensation.Efficiency capacitors increases with use of additional devices in the melting of ice on wires overhead lines and automatic inclusion of a reserve line to increase the capacity of mutually redundant transmission lines.In addition, reactive power compensation in distribution networks significantly improves its working mode voltage that is not always possible to provide regulators substations.After optimizing the parameters capacitors expedient to solve a qualitatively different mode of optimization problem